2013
DOI: 10.1007/s10295-012-1198-6
|View full text |Cite
|
Sign up to set email alerts
|

Production of organic acids by periplasmic enzymes present in free and immobilized cells of Zymomonas mobilis

Abstract: In this work the periplasmic enzymatic complex glucose-fructose oxidoreductase (GFOR)/glucono-δ-lactonase (GL) of permeabilized free or immobilized cells of Zymomonas mobilis was evaluated for the bioconversion of mixtures of fructose and different aldoses into organic acids. For all tested pairs of substrates with permeabilized free-cells, the best enzymatic activities were obtained in reactions with pH around 6.4 and temperatures ranging from 39 to 45 °C. Decreasing enzyme/substrate affinities were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 24 publications
1
20
1
1
Order By: Relevance
“…Perfis de diminuição de µ P menos acentuados foram observados com a utilização de temperaturas inferiores a 47°C. Zachariou & Scopes (1986) e Malvessi et al (2013) relataram a temperatura de 39°C como favorável para a conversão de substratos em produtos pelo complexo enzimático GFOR/GL, com a utilização de células livres de Z. mobilis. Como pôde ser observado, em se tratando de um sistema imobilizado, o fluxo da solução de substratos e produtos tem o comportamento afetado pela barreira representada pelo suporte, em elevada concentração celular no interior das esferas.…”
Section: Resultsunclassified
“…Perfis de diminuição de µ P menos acentuados foram observados com a utilização de temperaturas inferiores a 47°C. Zachariou & Scopes (1986) e Malvessi et al (2013) relataram a temperatura de 39°C como favorável para a conversão de substratos em produtos pelo complexo enzimático GFOR/GL, com a utilização de células livres de Z. mobilis. Como pôde ser observado, em se tratando de um sistema imobilizado, o fluxo da solução de substratos e produtos tem o comportamento afetado pela barreira representada pelo suporte, em elevada concentração celular no interior das esferas.…”
Section: Resultsunclassified
“…Nevertheless, the greatest commercial application is in the medical field, as the main constituent of fluid for organ preservation during the procedure of transplantation. Lactobionic acid is obtained industrially by dehydrogenation of the lactose using a metallic catalyst (Splechtna et al, 2001;Dhariwal et al, 2006;Paul and Patrick, 2009;Pedruzzi et al, 2011;Severo Júnior et al, 2011;Malvessi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown some alternatives for the production of lactobionic acid, as for example, biotechnological and electrochemical processes, both still in development (Miyamoto et al, 2000;Splechtna et al, 2001;Dhariwal et al, 2006;Severo Júnior et al, 2011;Malvessi et al, 2013). According to Jonas and Silveira (2004), a promising route for production of lactobionic acid is from lactose and fructose by enzymatic catalysis using permeabilized cells of Zymomonas mobilis.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Some reports show the use of the anaerobic bacterium Zymomonas mobilis to produce lactobionic acid / lactobionate. [10][11][12] This microorganism, presents in its periplasm the glucose-fructose oxidoreductase (GFOR, EC 1.1.99.28)/glucono-lactonase (GL, EC 3.1.1.17) complex. These enzymes operate on a ping-pong mechanism, in which lactose is oxidized to lactobiono-δ-lactone while fructose, which is employed as substrate for the regeneration of the NADPH cofactor, is reduced to sorbitol.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, by the action of GL, lactobiono-δ-lactone is hydrolyzed to lactobionic acid ( Figure 1). 11,13 In the bioproduction of lactobionic acid and sorbitol, using Z. mobilis GFOR/GL system, the pH of the reaction medium should be controlled in order to maintain the catalytic activity of the enzyme. As the lactobionic acid is formed, there is a tendency to decrease the pH and, for the maintenance of the catalytic activity, it should be kept at 6,4.…”
Section: Introductionmentioning
confidence: 99%